identity of success and Failure among middle school students - Ali Mohammed, Gibran Mohammed; Manoukh, Sabah Marshood (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of success identity and failure identity among the research sample of secondary school students in Sharqat and to identify the statistically significant differences according to the gender and specialization variables for the academic year (2023-2024). The researchers built a tool to measure success identity and a tool to measure failure identity. After extracting validity and calculating reliability, the Cronbach's alpha coefficient reached (0.88) and the retest (0.71) for success identity, while the failure identity reached (0.75) and the retest (0.72). Thus, the success identity scale became (30) paragraphs, and the failure identity scale (28) paragraphs in their final form for both scales. The two scales were applied to a random stratified sample of (280) male and female students. For the purpose of statistically processing the data, the researchers used Pearson's correlation coefficient and the t-test for one sample, and the t-test for the two independent samples. The results showed the presence of a level The average identity of success among middle school students. As for the identity of failure, it does not rise to the level of statistical significance, meaning that the research sample is not characterized by the identity of failure, and there are no statistically significant differences between males and females according to the gender variable, and there are no statistically significant differences between (scientific - literary) according to the specialization variable in the identity of success and the identity of failure, and the research came out with many recommendations and suggestions.